2012
DOI: 10.4103/1947-2714.98593
|View full text |Cite
|
Sign up to set email alerts
|

Cyanoacrylate glue dressing for hypospadias surgery

Abstract: Background:Hypospadias repair is a common pediatric operation. Several kinds of dressings are currently available, with their benefits and side effects.Aim:The aim of our study was to introduce a new method of dressing, by pouring several layers of cyanoacrylate (CA) glue as the dressing, in hypospadias surgery.Materials and Methods:Twenty out of the 61 patients with hypospadias, with a mean age of 13.5 months, were enrolled in this study. Forty-one had conventional dressing (pressure wrap dressing), while CA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Glubran Tiss2® is a two-component skin adhesive, based on NBCA (n-butyl 2 cyanoacrylate) and OCA (2-octyl cyanoacrylate). It is used in many clinical centres in Italy as a sealant of the PICC exit site, mainly because of its haemostatic effect ( 13 ), but also because it creates an efficient antiseptic barrier against the most diffused infective or pathogenic agents coming from the surrounding skin ( 14 ). The blend of the two monomers (NBCA+OCA) provides a high tensile strength and improves the elasticity ( 13 ) of the glue.…”
Section: Methodsmentioning
confidence: 99%
“…Glubran Tiss2® is a two-component skin adhesive, based on NBCA (n-butyl 2 cyanoacrylate) and OCA (2-octyl cyanoacrylate). It is used in many clinical centres in Italy as a sealant of the PICC exit site, mainly because of its haemostatic effect ( 13 ), but also because it creates an efficient antiseptic barrier against the most diffused infective or pathogenic agents coming from the surrounding skin ( 14 ). The blend of the two monomers (NBCA+OCA) provides a high tensile strength and improves the elasticity ( 13 ) of the glue.…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that UCF closure was achieved in 60% of our adhesive-treated UCF patients and in 68% of those treated surgically. Although the difference between groups in the successful UCF closure rate was not statistically significant, these results indicate clearly that the procedure should be included in the postoperative management of UCF and, as suggested by Lapointe et al [ 18 ], Prestipino et al [ 33 ], Tan et al [ 34 ] and Hosseini et al [ 35 ], should be regarded as an alternative to surgery for preventing or treating UCF. These observations support the results of simpler studies, such as those reported by Tsur et al [ 36 ] and Castañón García-Aliz et al [ 37 ].…”
Section: Discussionmentioning
confidence: 70%
“…The study found UCF recurrence in only four (11%) of the patients. Based on the waterproofing and moisture-resistance properties of the cyanoacrylate adhesives, Hosseini et al [ 35 ] undertook a case–control study in 61 children with a mean age of 13.5 months who underwent HSR using different techniques. Patients were divided into two groups: 41 children in whom conventional dressings were placed on the surgical site (control group) against 20 children in whom the suture lines were reinforced with NBCA+OCA (study group).…”
Section: Discussionmentioning
confidence: 99%
“…Many surgical techniques, as well as dressing models, were identified in the treatment of hypospadias [1][2][3][4]. An ideal dressing for hypospadias should be easy to apply and remove.…”
mentioning
confidence: 99%